Time of deliberation and space of power - Cassin, Barbara (Javnost (Ljubljana), 2005)
The conflict between Greece and Rome is one of modern history's first international conflicts. Writing in the second century AD, AElius Aristides views it as a discursive, linguistic and rhetorical conflict. Essentially, it can even be described as a conflict between silence and rhetoric. Rome, uniquevoice of Empire, is, in being a complying, fine-tuned orchestra, even more silent, and may be, already, our contemporary notion of consensus and ourversion of globalisation? Athens talks, debates, and retains the notion of the political as continuous creation of dissent. Hence Athens - or rhetoric - is victorious even when conquered.
Keywords: antični Rim; antična Grčija; mednarodni odnosi; mednarodni konflikti; communication; komuniciranje; politične komunikacije